1994
DOI: 10.1111/j.1399-6576.1994.tb04018.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol and thiopentone on polymorphonuclear leukocyte functions in vitro

Abstract: Anesthetic agents may impair host defense mechanisms including polymorphonuclear leukocyte (PMNL) function. We have studied the effects of thiopentone and propofol in low (thiopentone 10 mg/L, propofol 2 mg/l) and high (thiopentone 40 mg/L, propofol 6 mg/L) clinically relevant concentrations on PMNL adherence, chemotaxis, phagocytosis and killing in vitro. The results demonstrated that thiopentone in both concentrations significantly decreases all PMNL functions tested and had a direct influence on the PMNLs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
1
20
1
2
Order By: Relevance
“…Moudgil, Krunholz, Weiss and Skoultelia found that the phagocytosis and chemotaxis functions of neutrophils were suppressed when exposed to in vitro anaesthetics. As a result of decreased production of oxygen radicals, the intracellular killing process of bacteria is inhibited [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Moudgil, Krunholz, Weiss and Skoultelia found that the phagocytosis and chemotaxis functions of neutrophils were suppressed when exposed to in vitro anaesthetics. As a result of decreased production of oxygen radicals, the intracellular killing process of bacteria is inhibited [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, propofol produces a favourable sense of wellbeing in the patient. [31][32][33] Remifentanil is a synthetic opioid, with potent and selective m-opioid receptor agonist activity, that is rapidly metabolized in the blood and tissue, with an elimination half-life of $9 min. 34 Remifentanil was used in the present study as it has been used successfully in withoutmuscle relaxants anaesthesia, and maintains a stable haemodynamic state during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of anesthetic drugs on leukocytes is well documented [5][6][7][8][9][10][11]. Nishina et al [10] have recently reported that thiopental is able to inhibit leukocyte functions, This group has investigated leukocyte chemotaxis in a Boyden chamber assay (i. e. without endothelial cells).…”
Section: Introductionmentioning
confidence: 99%